2014
DOI: 10.1002/bab.1242
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of lipase on porous monodisperse chitosan microspheres

Abstract: Porous monodisperse chitosan microspheres were synthesized for enzyme immobilization. The microspheres were prepared using microchannels and modified with glutaraldehyde. The microspheres had a mean diameter of 495 µm; the polydispersity indices were less than 0.08, and the specific surface area was between 121 and 173 m(2) /g. Candida sp. 1619 lipase was selected as a model lipase. Immobilization conditions such as enzyme loading, glutaraldehyde concentration, and immobilization time were optimized. The tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Some scientists 17) demonstrated the synthesis of capecitabine-loaded semi-IPN hydrogel microspheres of chitosan-poly (ethylene oxideg-acrylamide) using GA and HCl solution. NaOH solution and GA solution also could be used as the cross-linkers by emulsion crosslinking method 18,19) . In our delivery system, vanillin and vitriolic acid were used as double cross-linkers.…”
Section: Discussionmentioning
confidence: 99%
“…Some scientists 17) demonstrated the synthesis of capecitabine-loaded semi-IPN hydrogel microspheres of chitosan-poly (ethylene oxideg-acrylamide) using GA and HCl solution. NaOH solution and GA solution also could be used as the cross-linkers by emulsion crosslinking method 18,19) . In our delivery system, vanillin and vitriolic acid were used as double cross-linkers.…”
Section: Discussionmentioning
confidence: 99%
“…The systems stored at 4 • C, after the analyzed time period, retain almost all of their original activity (96%), while immobilized lipase stored at 20 • C shows a decline in activity by approximately 10%. Chen et al [69] reported activity of lipase immobilized on chitosan microspheres at levels of 80% and 60% after storage at 4 • C for 5 and 20 days, respectively. Meanwhile Zhu et al [70] found that lipase immobilized on silica-coated magnetic nanoparticles preserved 70% of its initial activity after 20 days, when stored at 20 • C. The results obtained in our research indicate that immobilization of Candida antarctica lipase B on a silica-lignin support significantly extends its catalytic activity compared with the free enzyme and with previously published results.…”
Section: Storage Stabilitymentioning
confidence: 99%
“…Chitin is normally isolated from the exoskeletons of many species of insects and crustaceans [ 34 ]. Furthermore, chitosan is a biocompatible gel-forming cationic compound that can readily be prepared in different geometrical configurations, such as membranes, beads, nanoparticles by nano-immobilization [ 35 ], fibers, hollow fibers or sponges [ 15 , 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%